In vitro and in vivo Anticancer Activities of Folate-Decorated Vinorelbine Bitartrate-Loaded Recombinant Human Serum Albumin Nanoparticles - Wang, Wei; Li, Ling-yu; Zhao, Xiu-hua; Li, Nan; Fu, Yu-jie (Current Nanoscience, 2018)
Background: Vinorelbine bitartrate (VB), an important anticancer drug, is used to treat varieties of cancers in clinical, but its side effects when directly administered as an aqueous solution limit its application. Objective: To test anti-tumor activities of folate-decorated vinorelbine bitartrate-loaded recombinant human serum albumin nanoparticles (FA-rHSA-VBNPs). Method: A desolvation procedure was used to prepare vinorelbine bitartrate nanoparticles, then crosslinked with recombinant human serum albumin, and finally decorated with folic acid. The nanoparticles #39; surface morphology and particle size distribution were investigated in vitro. The in vitro antiproliferative activities were tested by the MTT assay, and the in vivo anti-tumor activities were investigated using S180 bearing mice. Result: We obtained spherical nanoparticles of 180 nm, and its size distribution was narrow. FArHSA- VBNPs and VB injection inhibited HO-8910, SK-OV-3, MCF-7, MX-1 and A-549 well, but showed little effect on Bel-7402, HepG-2 and PC-3. At 2 mg/kg, VB-FA-rHSANPs inhibited S180 by 83.20%, whereas VB injection inhibited 63.50%. Conclusion: In general, FA-rHSA-VBNPs exhibited much better cytotoxicity to all cancer cell lines than VB injection, and showed a dose-dependent effect in the survival towards the eight tumor cell lines. The cytotoxicity of FA-rHSA-VBNPs and VB injection on HO-8910 was significantly stronger than on the other seven human cancer cell lines. FA-rHSA-VBNPs showed much better anti-tumor activity against S180 than VB injection. FA-rHSA-VBNPs showed much better activities than VB injection both in vitro and in vivo anticancer tests.
Keywords: target delivery